Detection of viruses in the exotic shrimp Penaeus vannamei Boone, 1931 cultured in India - Rajeish, Y. Moger; NarasimhaMurthy, G.; Madhushree, Hoovinahalli Nataraju; Pujar, Basavareddy R.; Girisha, Shivani Kallappa; Suresh, T.; Venugopal, Moleyur Nagarajappa (Indian Journal of Fisheries, 2017)
Pacific white shrimp Penaeus vannamei Boone, 1931, is a recently introduced species in India. P. vannamei samples, collected from various shrimp farms of Karnataka, India were subjected to polymerase chain reaction (PCR) based detection of whitespot syndrome virus (WSSV), hepatopancreatic parvovirus (HPV), monodon baculovirus (MBV), infectious hypodermal and hematopoietic necrosis virus (IHHNV), taura syndrome virus (TSV) and infectious myonecrosis virus (IMNV). Out of the 81 shrimp samples analysed, 41 samples (50.6%) were found positive for WSSV and four (4.9%) were positive for IHHNV. Among 41 WSSV positive samples, 20 (48.7%) samples were found positive for WSSV by 1st step PCR, while the remaining 21 (51.2%) samples were positive by nested PCR. WSSV positive samples were further confirmed by dot blot hybridisation assay. However, clinical signs/disease symptoms were not observed in any of the shrimp samples tested positive for the viruses.